Mesothelin Sebagai Biomarker Deteksi Dini Kanker Pankreas - Fauziyyah Nuur Al azizah; Rizki Hanriko (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Abstract: Pancreatic cancer is difficult to diagnose at an early stage and generally has a poor prognosis. Surgical resection is the only potentially curing treatment for pancreatic carcinoma. To improve the prognosis of this disease, it is important to detect tumors at an early stage. The lack of sensitive and specific tumor markers for early diagnosis has a major contribution to the poor prognosis. For this reason, it is necessary to make an early diagnosis of pancreatic cancer through a biomarker in the form of mesothelin which can be found in the blood and urine. Mesothelin is a glycoprotein that is expressed in normal mesothelial cells but is overexpressed in pancreatic cancer. How to check mesothelin levels in the blood can use ELISA and for those in the urine can use spectrophotometry. And mesothelin has been shown to increase in early stage cancer and 64% in metastatic cancer. Mesothelin can also be expressed in other organs such as endometrioid adenocarcinoma (59-64%), cervix (25%), pancreas (86-100%), colorectal (28-50%), esophagus (25-46%) and gastric carcinoma (27-58%) but in pancreatic cancer the amount of mesothelin produced is greater. Therefore mesothelin can be an early detection biomarker that is useful for pancreatic cancer Keywords: biomarkers, mesothelin, blood, urine, overexpression